(untitled) (Journal of Surgical Sciences, 2020)
Background: The number of postgraduate students in Cardiac surgical discipline is increasing day by day with incremental proportion are measurably suffering from the unnecessary lingering of the present course curriculum. The primary objective of this study was to find out the last 5 years’ of results of Masters in Surgery course under the University of Dhaka from a student room survey. A secondary objective was to find out positive changes that could show us the way of a step toward up-gradation. Methods: It is a retrospective analysis of all examination results of Cardio-vascular & Thoracic Surgery published since January 2008 to January 2013 from the University of Dhaka with in depth interview of 11 participants. Results: 85.24% students failed to pass part-I of Masters in Surgery for Cardio-vascular & Thoracic Surgery course while, 82.18% in part-II and 71.28% failed to pass the final part. Average 2.51 attempts needed to complete each part of the designed course resulted into lingering of course duration for 42.18 months/student. In the thoracic surgery discipline the number of students alarmingly reduced up to 0% in the recent academic sessions. Conclusions: Masters in Surgery is resulting in unnecessary prolongation of the course. We should step forward to meet the next generation challenge. Journal of Surgical Sciences (2019) Vol. 23(2): 71-74